Evaluating Achievement Gaps Between Monolingual and Multilingual Students. (October 2021) - Goodrich, J. Marc; Thayer, Lauren; Leiva, Sergio
This study represents an extension of the findings of Kieffer and Thompson (2018) and evaluates potential correlates of state- and district-level achievement gaps in reading and mathematics between monolingual and multilingual students. Using data from the National Assessment of Educational Progress, this study reported that there were substantial achievement gaps that were narrowing over time at the state level but that there were no achievement gaps between monolingual and multilingual students in large school districts. Larger numbers of dual language programs were associated with smaller achievement gaps. State achievement gaps narrowed more over time for states with larger numbers of multilingual students. Implications and directions for future research are discussed.